Letter from James L. Hansen to Thomas H. Kent regarding bird sightings, November 25, 1980 - Hansen, James L.et al (1980)
Field notes contributed by James L. Hansen in a letter to Thomas H. Kent. Highlights of the field notes include a deceased Cinnamon Teal at Zirbel Slough. Epson - sheet feed